Pleiotropic effects of Mentha longifolia L. extract on the regulation of genes involved in inflammation and apoptosis induced by Clostridioides difficile ribotype 001 - Raeisi, Hamideh; Azimirad, Masoumeh; Abdemohamadi, Elham; Pezzani, Raffaele; Zali, Mohammad Reza; Yadegar, Abbas (Frontiers in Microbiology, 2023)
The dramatic increase in multidrug-resistance of Clostridioides difficile isolates has led to the search for new complementary medicines against C. difficile infection (CDI). In this study, we aimed to examine the inhibitory effects of hydroethanolic extract of Mentha longifolia L. (ETOH-ML) on the growth of C. difficile RT001 and its toxigenic cell-free supernatant (Tox-S)-induced inflammation and apoptosis. The active phytochemical components of ETOH-ML were detected using GC and HPLC. The antimicrobial properties of the extract were examined against C. difficile RT001. Furthermore, cell viability and cytotoxicity of Caco-2 and Vero cells treated with various concentrations of ETOH-ML, Tox-S of C. difficile RT001, and their combination were assessed. Anti-inﬂammatory and anti-apoptotic activities of ETOH-ML were explored in Tox-S stimulated Caco-2 cells using RT-qPCR. Based on our results, rosmarinic acid was the main phytochemical component of ETOH-ML. The extract showed significant antimicrobial activity against C. difficile RT001 by agar dilution and broth microdilution methods. Moreover, ETOH-ML at concentrations of ˂25 μg/ml had no significant effect on cell viability compared to untreated cells. Treatment cells with the extract (10 or 25 μg/ml) significantly increased the cell viability and reduced the percentage of cell rounding in Caco-2 and Vero cells treated by Tox-S, respectively (P <0.0001). Co-treatment of Tox-S stimulated Caco-2 cells with ETOH-ML showed significant anti-inflammatory and anti-apoptotic activities by downregulating the gene expression level of IL-8, IL-1β, TNF-α, iNOS, TGF-β, NF-κB, Bax, and caspase-3, while upregulating the expression level of Bcl-2. Our results demonstrated for the first time the antimicrobial, anti-inﬂammatory, and anti-apoptotic effects of M. longifolia extract on C. difficile RT001 and its Tox-S. However, further research is needed to evaluate the potential application of M. longifolia extract on CDI treatment in clinical setting.